Effect of Stevia and Erythritol on Sensory, Microbiological, and Physicochemical Characteristics of Black Glutinous Rice Cookies - Sulistyawati, Eko Yuliastuti Endah; Rismaya, Rina; Fauziyyah, Athiefah; Ulfah, Mutiara (Journal of Applied Agricultural Science and Technology, 2024)
Cookie is a popular and well-liked food but is high in calories and low in fiber. Replacing sugar by artificial sweeteners in cookies is expected to reduce the calorific value of cookies. This study aimed to evaluate the effect of adding artificial sweeteners on the physical, sensory, microbiological characteristics, and functional benefits of cookies. A completely randomized design with sweeteners (stevia and erythritol) and concentrations (0.2%, 0.4%, and 0.5%) was used. The results showed that stevia and erythritol had significantly affected all test parameters, except in the mold/yeast parameters of cookies. The adding of stevia and erythritol significantly decreased L*, a*, b*, hedonic scores, caloric values, dietary fiber contents, total microbial values but significantly increased hardness and antioxidant capacities (IC50) of final cookies. All sensory ratings of the sucrose and formulated cookies were >3 points, which demonstrated that stevia and erythritol can be sugar replacers that can reduce calorie cookies. The findings can guide in the reformulation of low-calorie, high-fiber, and non-gluten cookies.